Popliteal artery aneurysm is a cause that should not be forgotten in acute limb ischemia - Deniz Sarp Beyazpinar; Mehmet Emir Erol (Turkish Journal of Vascular Surgery)
Aim: The aim of our study is to determine the amputation rates in patients with acute limb ischemia (ALI) who were monitored for one year and to identify the factors influencing these rates, as well as to examine the effects of popliteal artery aneurysm (PAA) on acute limb ischemia. Material and Methods: Between January 2022 and January 2023, a retrospective analysis was conducted on 103 patients who presented to our clinic with ALI. Among patients, 59.2% (n=61) were not amputated and classified as Group-1. Group-2 comprised 40.8% of the patients (n=42) all of whom required amputation in the follow-up period. Cases of ALI attributable to atrial fibrillation and trauma were excluded from the study. Both groups were compared in terms of amputation rates in the follow-up period and demographic characteristics. All patients were Rutherford Stage IIa and IIb. Unsalvageable Rutherford Stage3 patients were also excluded. All patients who underwent amputation had exclusively undergone embolectomy; no amputations were observed in patients with PAA (p=0.01). Results: The average age of the patients was 70.01±12.56 years (min 31-max 89). Seventy-five patients were male (72.8%), while twenty-eight patients were female (27.2%). The etiology of ALI was identified as thromboembolic events secondary to atherosclerotic peripheral artery disease (APAD) in 92 patients (89.3%), and as PAA in 11 patients (10.7%). Sixty-six (64.7%) patients underwent solely embolectomy, nine (8.7%) patients received combined embolectomy with thrombolytic therapy and twenty-eight patients (27.4%) patients underwent surgical revascularization. In the first year follow-up, 42 (41.2%) patients had undergone amputation. All patients who underwent amputation had exclusively undergone embolectomy; no amputations were observed in patients with PAA (p=0.01). Conclusion: Blinded embolectomy may be the first line surgical treatment for ALI but it has higher amputation rates in 1-year follow-up. While PAA is considered one of the rare causes of ALI, it should be kept in mind as one of the etiological factors in patients presenting with ALI. With appropriate treatment, amputation rates are significantly lower in patients with PAA. [Turk J Vasc Surg 2024; 33(2.000): 84-87]